Keys to Successful Orthotopic Bladder Substitution - Studer, Urs E. (Springer International Publishing : Imprint: Springer, 2015)
This book provides clear guidance on how to achieve excellent functional results and avoid failures when performing cystectomy and orthotopic bladder substitution. The opening sections present helpful checklists relating to patient selection, preoperative management, the procedures themselves, intraoperative measures, postoperative management, and actions to be taken in the event of various symptoms and complications. The remainder of the book focuses in detail on a variety of specific points of interest such as how and why to attempt a nerve-sparing cystectomy, the role of pelvic lymph node dissection, physical and physiological considerations relevant to reservoir construction, metabolic consequences of the incorporation of bowel into the urinary tract, preservation of renal function, and quality of life issues. The information provided may not only be instrumental to urologists, but also to specialized health care professionals, as well as the concerned patients.